The Validity of Notarial Deeds Using Cyber Notary in Making Authentic Deeds Based on Legal Perspectives in Indonesia - Monika, Julia; Hafidz, Jawade (Jurnal Konstatering, 2025)
This study employs normative legal research with a statutory, analytical, and theoretical approach. Secondary data includes primary legal materials (the Electronic Information and Transactions Law, the State Law on the Provision of State Assets, the Civil Code, and other implementing regulations), secondary legal materials (literature and previous research), and tertiary legal materials (dictionaries and encyclopedias). Library research was used as the data collection method, while prescriptive data analysis provides arguments and legal assessments of the findings. The results of this study are expected to provide both theoretical and practical contributions to the development of digital notary law in Indonesia. Theoretically, this research can enrich scientific studies in the legal field, particularly regarding the adaptation of notary legal norms to developments in information technology. Meanwhile, practically, the findings of this study are expected to serve as a reference for policymakers, notary professional organizations, and legal practitioners in formulating more comprehensive and applicable regulations related to the implementation of Cyber Notary, thereby ensuring legal certainty, legal protection, and efficiency in the implementation of notary duties in the digital era.